The molecular evolutionary dynamics of the vomeronasal receptor (class 1) genes in primates: a gene family on the verge of a functional breakdown - Yoder, Anne D. (Front Neuroanat, 2014)
Olfaction plays a critical role in both survival of the individual and in the propagation of species. Studies from across the mammalian clade have found a remarkable correlation between organismal lifestyle and molecular evolutionary properties of receptor genes in both the main olfactory system (MOS) and the vomeronasal system (VNS). When a large proportion of intact (and putatively functional) copies is observed, the inference is made that a particular mode of chemoreception is critical for an organism’s fit to its environment and is thus under strong positive selection. Conversely, when the receptors in question show a disproportionately large number of pseudogene copies, this contraction is interpreted as evidence of relaxed selection potentially leading to gene family extinction. Notably, it appears that a risk factor for gene family extinction is a high rate of nonsynonymous substitution. A survey of intact vs. pseudogene copies among primate vomeronasal receptor Class one genes (V1Rs) appears to substantiate this hypothesis. Molecular evolutionary complexities in the V1R gene family combine rapid rates of gene duplication, gene conversion, lineage-specific expansions, deletions, and/or pseudogenization. An intricate mix of phylogenetic footprints and current adaptive landscapes have left their mark on primate V1Rs suggesting that the primate clade offers an ideal model system for exploring the molecular evolutionary and functional properties of the VNS of mammals. Primate V1Rs tell a story of ancestral function and divergent selection as species have moved into ever diversifying adaptive regimes. The sensitivity to functional collapse in these genes, consequent to their precariously high rates of nonsynonymous substitution, confer a remarkable capacity to reveal the lifestyles of the genomes that they presently occupy as well as those of their ancestors.